2007
DOI: 10.1093/aob/mcm255
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Epicuticular and Intracuticular Wax Layers on Adaxial Sides of Rosa canina Leaves

Abstract: A gradient exists between the composition of the epi- and intracuticular wax layers of Rosa canina leaves. This gradient may result from polarity differences, in part caused by differences in chain lengths. The outer wax layer accessible to the phyllosphere showed a unique composition of wax compounds. The ecological consequences from such a gradient may now be probed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 33 publications
2
63
0
4
Order By: Relevance
“…lacking surface wax crystals) and alicyclic wax constituents (Buschhaus and Jetter, 2011). In five cases, namely for tomato fruits and for leaves of P. laurocerasus, Rosa canina, Ligustrum vulgare, and M. tanarius, pentacyclic triterpenoids had been found at high concentrations in the intracuticular wax only (Jetter et al, 2000;Jetter and Schäffer, 2001;Vogg et al, 2004;Guhling et al, 2005;Buschhaus et al, 2007aBuschhaus et al, , 2007bZeisler and Schreiber, 2016).…”
mentioning
confidence: 99%
“…lacking surface wax crystals) and alicyclic wax constituents (Buschhaus and Jetter, 2011). In five cases, namely for tomato fruits and for leaves of P. laurocerasus, Rosa canina, Ligustrum vulgare, and M. tanarius, pentacyclic triterpenoids had been found at high concentrations in the intracuticular wax only (Jetter et al, 2000;Jetter and Schäffer, 2001;Vogg et al, 2004;Guhling et al, 2005;Buschhaus et al, 2007aBuschhaus et al, , 2007bZeisler and Schreiber, 2016).…”
mentioning
confidence: 99%
“…Subsequent solvent extraction releases additional wax that presumably resided within the cutin and is called intracuticular wax. Several studies have revealed that wax composition typically is not uniform between the two wax layers (Gniwotta et al, 2005;Guhling et al, 2005;Buschhaus et al, 2007a;Buschhaus et al, 2007b;Ji and Jetter, 2008;van Maarseveen and Jetter, 2009). Most notably, cyclic compounds regularly accumulate almost exclusively in the intracuticular wax layer.…”
mentioning
confidence: 99%
“…For example, Buschhaus et al (2007b) reported alkanes, primary alcohols, alkyl esters, triterpenoids and minor components in the waxes of rose leaves. GC analysis was carried out with the temperature programmed to rise from 50 °C to 320 °C and held for 30 min at 320 °C.…”
Section: Gc Separation and Detection Of Cuticular Waxesmentioning
confidence: 99%